Chromosome aberrations in psoriatic patients treated with arsenic - Nordenson, I; Salmonsson, S; Brun, E; Beckman, G (Human Genetics, 1979)
A significantly increased frequency of chromosomal aberrations was found in lymphocytes from eight psoriatic patients previously treated with arsenic than in lymphocytes from eight psoriatics with no such previous treatment. In most patients the arsenic therapy was discontinued more than 15 years ago. In the arsenic-treated group a statistically significant heterogeneity was found with respect to the frequency of aberrations. The frequency of sister chromatid exchange was not increased in the arsenic-treated patients.
Keywords: Adult; Aged; Arsenic/adverse effects; Chromatids/drug effects; Chromosome Aberrations; Crossing Over, Genetic/drug effects; Female; Humans; Lymphocytes/ultrastructure; Male; Middle Aged; Psoriasis/drug therapy; Time Factors